2016
DOI: 10.1002/aenm.201601420
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dangling Bonds in Photodegraded Polymer:Fullerene Solar Cells

Abstract: conversion efficiency (PCE), [1][2][3][4][5][6][7][8] up to ≈11.5%, was achieved by, e.g., using low bandgap polymers [1][2][3][4][5][6] and developing approaches to control the active layer's morphology utilizing thermal [7] or solvent annealing, [8] mixed solvents, [4] or additives. [1][2][3][4][5][6] Low bandgap polymers improve the PCE by absorbing more sunlight, increasing the short circuit current density J sc (the value without applied bias). A larger open circuit voltage V oc (the forward bias that zer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…The photodegradation of PSCs has been recently attributed by some solely to effects triggered by charge collection layers and interfaces 49 and by others to hot carriers breaking C-H bonds at the donor/acceptor interface. 29 The latter claim required energies 44 eV, but we showed here that the monomers themselves are unstable to UV irradiation, which certainly does not involve homolytic cleavage of C-H bonds. If hot carriers were breaking apart C-H bonds, then almost no polymer would be stable, but that is not the case.…”
Section: Device Stabilitymentioning
confidence: 75%
See 1 more Smart Citation
“…The photodegradation of PSCs has been recently attributed by some solely to effects triggered by charge collection layers and interfaces 49 and by others to hot carriers breaking C-H bonds at the donor/acceptor interface. 29 The latter claim required energies 44 eV, but we showed here that the monomers themselves are unstable to UV irradiation, which certainly does not involve homolytic cleavage of C-H bonds. If hot carriers were breaking apart C-H bonds, then almost no polymer would be stable, but that is not the case.…”
Section: Device Stabilitymentioning
confidence: 75%
“…There is a lack of studies on degradation mechanisms 23,24 in general and in devices, thus, very little was done on the degradation and stability of this class of materials [25][26][27] and much less on the degradation and stability of their devices. 28,29 Semiconducting polymers generally degrade, especially under visible light illumination, resulting in steady buildup of free radical species as shown by Frolova et al 30 with studies on PTB7 and PBDTTT-CF. It is also shown that the presence of additives, in particular DIO, in the active layer of organic solar cells accelerates the degradation mechanism 31 in these devices.…”
Section: Introductionmentioning
confidence: 97%
“…We detected no ESR signals that were expected [17] from PC61BM (gx = 2.0060, gy = 2.0028, gz = 2.0021), or PEDOT:PSS [8] (g = 2.0037) before and after illumination. We observed no photo generated carbon dangling radicals [17] with a g-value of 2.0029 which clearly establishes that the signals we observed did not originate from the over layers. Therefore, the only source that can give rise to such signals is the underlying UV-ozone treated glass substrate.…”
Section: Resultsmentioning
confidence: 65%
“…The correlation between increasing EDMR signal and decreasing cell performance is in agreement with previous EPR studies which showed that the higher concentrations of paramagnetic radical species the lower the cell performance. [21][22][23] The absolute magnitude of the spin-dependent current change (in amperes) is obscured when using phase sensitive detection, as it is dependent on the eld modulation amplitude. However, for the DIO processed air exposed cell the change of the DC photocurrent (short circuit) could be measured and decreased by approximately 50 nA on resonance (using a microwave power of 200 mW).…”
Section: Cwedmrmentioning
confidence: 99%